Pengaruh Co- branding dan FoMO terhadap Impulse Buying Gen Z pada Produk Kolaborasi Nabati dengan Girl Group Kpop Aespa di Surabaya - Alfiatus Zainiyah; Ayun Maduwinarti; Ute Cahirus M.Nasution (Politeknik Kampar, 2025)
The rapid development of the bussines world requires companies to contiously innovate in order to remain competitive. Collaboration with Kpop artists have become a popular marketing strategy to attract consumers, as a demonstrated by PT Kaldu Sari Nabati Indonesia through its partnership with the girl group Aespa. This collaboration utilized co- branding strategies and leverages the Fear of Missing Out (FoMO) phenomenon, particularly prevalent among generation Z, potentially triggering impulse buying behavior. This study aims to examin the influence of Co- branding and FoMO on impulse buying behavior toward the Nabati with Aespa collaboration product in Surabaya. The research uses a quantitative approach with a questionnaire as the research instrument. The sample consist 100 generation Z repondents who have purchased the collaborative product, selected using purposive sampling. The result show that co- branding and FoMO have a significant effect, both partially and simultaneously, on impulse buying contributing 40,2% to the behavior. The reamaing influence is a attributed to other factor such as exclusive packing design and digital marketing. This study suggest that future researchers explore additional variabels and broaden the sample and population for deeper analysis.